Qualitative methods in psychology : a research guide - Banister, Peter 1947- (Berkshire [England] : Open University Press, 2011)
This book is a collaborative production, based on the experiences of the co-authors in presenting a course in qualitative methods over many years to MSc students. This is not an edited book; the authors have drafted particular chapters, but the team has collectively discussed, reworked and rewritten the text to produce a coherent review and guide to the area. This research guide is designed to be an introductory text to qualitative methods, intended for advanced undergraduate and postgraduate students.
As well as furnishing an understanding of the assumptions underlying such research methods, the book is intended to present a practical guide as to how to carry out qualitative investigations, and in addition to provide the basis for a critical evaluation of these methods.
Orientations: Phenomenology; Action research; Positionalities -- Methodologies: Observation; Ethnography; Interviewing; The repertory grid and its possibilities; Psychosocial analysis; Narrative inquiry; Historical analyses -- Representations: Future directions for qualitative research ; New and emerging forms of representation; Writing up; Problems in/of qualitative research.
Includes bibliographical references and index.
Keywords: Psychology -- Research -- Methodology